Environmental enrichment: a systematic review on the effect of a changing spatial complexity on hippocampal neurogenesis and plasticity in rodents, with considerations for translation to urban and built environments for humans - Khalil, Mohamed Hesham (Frontiers in Neuroscience, 2024)
This systematic review investigated the impact of spatial complexity on neurogenesis and hippocampal plasticity in rodents, discussing the translatability of these findings to human interventions. A search of PubMed, Web of Science, and Scopus identified 32 studies meeting the eligibility criteria. The studies evaluated various models of spatial complexity in rodents, including environmental enrichment, changes to in-cage elements, complex layouts, navigational mazes featuring novelty and intermittent complexity. A regression equation was formulated to synthesize key factors influencing neurogenesis, such as duration, physical activity, frequency of changes, age, living space size, and temperature. Home-cage enrichment and models like the Hamlet complex maze and the Marlau cage offer insight into how architectural design and navigational complexity can impact neurogenesis. While evidence on intermittent spatial complexity in humans is limited, data from the pandemic lockdowns provide preliminary evidence. Findings underscore the cognitive benefits of spatial complexity interventions and inform future translational research. Existing equations relating rodent and human ages may allow rodent-human translation of the duration of enrichment protocols. This comprehensive review elucidates the dynamic interplay between spatial complexity and neurogenesis and offers insights beyond proliferation. It paves the way for architectural design, interior design, and urban planning approaches that optimize cognitive health and well-being through strategic manipulation of spatial complexity. By incorporating these findings and utilizing the newly developed regression model, interventions targeting human subjects at various life stages, from early childhood to adulthood, could effectively stimulate adult hippocampal neurogenesis. Additionally, for aging individuals, enrichment interventions hold promise for achieving cognitive reserve or even reversing cognitive decline.